(untitled) (Research, Society and Development, 2020)
The increase in the number of records of congenital syphilis has been a public health concern. Data from the World Health Organization (WHO) estimate that in 2016 there were 20 million cases of syphilis in adolescents and adults, with 6.3 million new cases. In Brazil, in 2017, there were 59.1 cases per 100,000 inhabitants and in 2018 75.8 / 100,000 inhabitants. In children it is transmitted vertically by the mother who has the bacterium Treponema pallidum. Thus, the reduction in the number of cases of pregnant women with congenital syphilis is essential so that newborns do not also present this pathology and its consequences. In addition, it is worth mentioning pregnant adolescents who have more risk factors in relation to syphilis, such as the rebelliousness of puberty and the lack of information about safe sex and, therefore, deserve special attention. The present study aims to review the literature regarding the growth of cases of syphilis, taking into account the increase in pregnant women with syphilis and the consequences suffered by the newborn.